Effect of Sublethal Concentration of Dimecron on Vitamin C Content in Tissues of Lamellidens corrianus - A.N., Kulkarni; R., Keshavan (Fishery Technology, 2025)
Fresh water mussel, Lamellidens corrianus was exposed to three sublethal concentra tions 0.4x10-2,0.8x1 (TZ and 1.2x10-2%) of Dimecron, an organophosphate insecticide for 24,48,72 and 96 h. Changes in vitamin C content were observed after each exposure period. Vitamin C content was observed to decrease in hepatopancreas, gill and foot. Changes in vitamin C content are discussed in relation to exposure period and concentration of Dimecron.